Therapetic experience of hyperbaric oxygenation in ulcerative colğitis refactory to medical treatment (Case report) - Saadettin HÜLAGÜ,; Levent DEMİRTÜRK,; Melih ÖZEL,; Kadir DÜNDAR,; Mehmet ALTIN, (Turkish Journal of Gastroenterology, 2019)
-